SYSTEMATIC LITERATURE REVIEW TERHADAP KERANGKA TATA KELOLA KEAMANAN DAN PRIVASI BERBASIS RISIKO PADA EKOSISTEM SMART CITY DAN SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK (SPBE) - Agus Indra Cahaya; Taufik Fredy Kristianto; Aji Supriyanto (Smart Education, 2026)
This study aims to identify, evaluate, and synthesize risk-based security and privacy governance frameworks implemented in Smart City and Electronic-Based Government System (SPBE) ecosystems. The method used is a Systematic Literature Review (SLR) by adapting PRISMA guidelines on selected literature related to Smart City, e-Government, cybersecurity, privacy, Internet of Things (IoT), Big Data, and risk management. The literature extraction results indicate that the implementation of integrated security governance frameworks such as ISO/IEC 27001, NIST Cybersecurity Framework, ENISA guidelines, and risk-based evaluation models was identified as an important factor in improving information security maturity and mitigating privacy risks in digital public services. Furthermore, the increasing integration of IoT devices, Big Data platforms, and interconnected public service infrastructures introduces new security challenges that require comprehensive governance approaches. The findings indicate that successful Smart City and SPBE implementation requires integrated risk-based security and privacy governance frameworks. Furthermore, this study proposes a conceptual framework that may serve as an initial reference for developing secure, adaptive, and sustainable digital public services.